A moderate reduction in irrigation and nitrogen improves water-nitrogen use efficiency, productivity, and profit under new type of drip irrigated spring wheat system - Wan, Wenliang; Zhao, Yanhui; Li, Xiaofang; Xu, Jing; Liu, Kaige; Guan, Sihui; Chai, Yaqian; Xu, Hongjun; Cui, Hongxin; Chen, Xianjun; Wu, Pei; Diao, Ming (Frontiers in Plant Science, 2022)
Rational irrigation and nitrogen management strategies are crucial for wheat growth. However, the optimal amount of water and nitrogen for the newly developed drip irrigated spring wheat system (TR6S, one drip tube service for six rows of wheat, with a row spacing of 10 cm and an inter-block space of 25 cm, saves drip tubes and obtains higher profits) in dry and semi-arid areas remains unclear. Therefore, a field experiment was conducted with four nitrogen levels (300, 270, 240, and 0 kg ha−1 referred N300, N270, N240, and N0) and four irrigation levels (4500, 4200, 3900, and 3600 m3 ha−1 referred I4500, I4200, I3900, and I3600) during the 2021–2022 and 2022–2023 spring wheat seasons to analyze the effects of irrigation (I) and nitrogen (N) levels on grain yield, water-nitrogen use efficiency, profit, biomass accumulation, and nitrogen nutrient absorption status under TR6S. Compared with the traditional irrigation and nitrogen management strategy (N300–I4500, as control), lesser irrigation and nitrogen supply (I＜3979 m3 ha−1 and N＜273 kg ha−1) saved cost but led to lower grain yield, water use efficiency (WUE), agronomic efficiency of nitrogen fertilizer (AEN), and profit. However, a moderate reduction in irrigation and nitrogen supply (4500 m3 ha−1＞I＞3979 m3 ha−1 and 300 kg ha−1 ＞N＞273 kg ha−1) improved grain yield, WUE, AEN, and profit. The increase in grain yield was mainly related to the rise in 1000-grain weight and kernels per spike. Although the moderate reduction in irrigation lowered soil moisture status, the dry matter pre-stored in the vegetative organs before anthesis that gets redistributed into grains during grain filling was improved. Moreover, the moderate reduction in nitrogen supply resulted in a more reasonable nitrogen nutrition index (NNI) of wheat plant, which improved flag leaf area and chlorophyll relative content (SPAD) at the anthesis stage. This also played a positive role in biomass accumulation and redistributed, yield structure optimization. Considering comprehensively yield, WUE, AEN and profit, combination of 285 kg ha−1 N and 4170 m3 ha−1 I was optimal irrigation and nitrogen application pattern for TR6S. This strategy can be applied to other arid and semi-arid regions.